ZONASI JANGKAUAN PELAYANAN PUSKESMAS TERHADAP PASIEN COVID-19 DI KOTA KUPANG - Punuf, Defritus Aldrin; Rahmawati, Arfita; Pamungkas, Bella Theo Tomi (Jurnal Geografi, 2021)
Covid-19 is a challenge by the people of Indonesia today. Since the Covid-19 pandemic has hit Indonesia in February 2020, covid-19 became a pandemic because the events of this pandemic spread almost throughout Indonesia with a death rate of 2.39%. One of the provinces affected by the Covid-19 pandemic, namely East Nusa Tenggara Province with the highest Covid-19 cases, was in Kupang City. Puskesmas as health facilities closest to the community have an important role in provide services to reduce the death rate due to Covid-19. This study aims to map the zoning of the puskesmas reach to Covid-19 patients in Kupang City using multiple ring buffer analysis. The results showed that the reach of puskesmas services to Covid-19 patients in Kupang City was included in the very affordable category with a distance of 0 - 2.5 km to reach 69.55% of Covid-19 patients. There are unreachable category area in puskesmas services in a small part of the southwest part of Alak Village and the southeastern part of Kolhua Village.